Kualitas dan Potensi Beberapa Kaplet/Tablet/Kapsul Antibiotik Pemenang e-Katalog 2017, Obat Sejenis Pengganti dan Originatornya - Prih Sarnianto; Syarmalina Syarmalina; Ferannisa Firdaus; Rike Farahiyah; Mustiko Aji Punto Baskoro; Esa Aulia Rizkita (Fakultas Farmasi Universitas Pancasila, 2022)
The price of drugs that win the e-Catalogue tender has long been considered too low by some pharmaceutical companies, and some even below their production cost. On the other hand, the fact that only pharmaceutical products with BPOM distribution licenses are eligible for the price tender, the quality of such e-Catalogue winners should not be of concern. This study aimed to evaluate the quality of several items of antibiotic products, an important drug category that can cause serious impacts if its quality is compromised. Samples used in the study were product items with the highest demands: Amoxicillin 500 mg, tetracycline 500 mg, cefadroxil 500 mg, and ciprofloxacin 500mg listed in the e-Catalogue 2017 as well as their generic and branded generic (OND) alternatives, and its respective originators. The quality parameters of the samples were evaluated according to the Indonesian Pharmacopoeia 5th Edition (FI-V). Antibiotic potency assays were conducted by using the Plate-Cylinder Method with S. aureus ATCC 25922 and E. coli ATCC 6538 as the testing bacteria. The results showed that all samples met the FI-V requirements on antibiotic content, weight uniformity, disintegration time, and dissolution. However, antibiotic potency of the e-Catalogue 2017 winners tend to be lower than their generic and OND alternatives as well as their respective originators, with a wide disparity: 10.3–18.2 percentage points, or a relative disparity of 12.0–26.4%, except for amoxicillin 500 mg caplet, in the assays using S. aureus. In conclusion, tetracycline 500 mg, cefadroxil 500mg, and ciprofloxacin 500 mg caplets/tablets/capsules listed in the e-Catalogue 2017 contain active pharmaceutical ingredients of lower qualities than their more expensive alternatives